THE LIFE OF MUSLIM INDONESIAN STUDENTS IN GERMANY: CHALLENGES AND OPPORTUNITIES - Gilang Maulana Majid (Jurnal Kajian Wilayah, 2017)
Immigration of people attached to a certain religion in a country where most of the population do not embrace the same religion has always been an interesting topic to explore, especially when it is regarding the discourse of student mobility in higher education world. A lot of factors must be taken into account before one makes a decision on which country to continue the study. As Muslims adhere to certain religious values, any factor that supports one’s piousity would be ideally weighed. This study explores the life of Muslim Indonesian students studying in Germany. Departing from the study motivation, the concept of push and pull factor is then enriched with religious perspectives. The research findings show that even though there are challenges that these students face as a Muslim, there is still an interesting opportunity that they have experienced when residing in Germany and later deem most significant in relation to their Islamicity. Realizing the importance of this kind of discourse for Indonesian immigrants, be it student or non-student, a suggestion of further research under the same topic is emphasized. Keywords: Germany, Hajj, higher education,Muslim Indonesian student, push-pull factor AbstrakImigrasi orang-orang yang melekat pada agama tertentu di negara yang mana sebagian besar penduduknya tidak memeluk agama yang sama selalu menjadi topik yang menarik untuk dieksplor, terutama ketika menyangkut wacana mobilitas siswa di dunia pendidikan tinggi. Banyak faktor harus diperhitungkan sebelum seseorang membuat keputusan ke negara mana untuk melanjutkan studi. Sebagai umat Islam yang mematuhi nilai-nilai agamanya, setiap faktor yang mendukung kesalehan seseorang akan dipertimbangkan. Studi ini mengeksplorasi kehidupan pelajar Indonesia Muslim yang belajar di Jerman. Studi ini berangkat dari motivasi belajar, konsep push dan pull factor yang kemudian diperkaya dengan perspektif agama. Temuan penelitian menunjukkan bahwa meskipun ada tantangan yang dihadapi para siswa ini sebagai seorang Muslim, namun masih ada peluang menarik yang mereka alami ketika tinggal di Jerman yang kemudian dianggap sangat penting dalam kaitannya dengan keislaman mereka. Menyadari pentingnya wacana semacam ini bagi para imigran Indonesia, baik itu mahasiswa maupun non-pelajar, maka perlu penelitian lebih lanjut dengan topik yang sama.Kata kunci: Mahasiswa Muslim Indonesia, Jerman, push-pull factor,pendidikan tinggi, Haji